Aplicação de jogo de empresas: um experimento com geração randômica de cenários em sistemas dinâmicos - Colombo, Roberto (2003)
This work presents the development and practical experimentation of an application software for a business game, based on the coupling of two models: one for a generic enterprise which is built in the System Dynamics paradigm and the other one built in a spreadsheet application which acts as a randomic scenario generator. This game can be used in a single user or in a multiuser version. The randomic and automatic scenario generation provides a more effective environment for the learning and training goals of the participants.